The Measurement of Impulse Buying toward Emotional Responses - Joseph M J Renwarin (Publisher Cv. Inara, 2021)
The objective of this research aims to know the influence of sales promotions and store atmosphere towards impulse buying with emotional responses as an intervening variable. The research method explores the primary data using quantitative approach for analysis. The research data of 310 respondents, come from the questionnaire disbursement by google form. The data analysis using SPSS 23.0 and SEM methods (Structural Equation Modeling) 88.0 LISREL. The research results of the analysis stated that sales promotions has no effect towards impulse buying with t value 1.28 (< 1.967); store atmosphere has no effect towards impulse buying with a t value -2.25 (< 1.967); emotional responses affect the impulse buying with t value 4.56 (> 1.967); sales promotion affect to emotional responses with t value 7.68 (> 1.96) and store atmospheric affect on impulse buying with value t of 10.12 (>1.967).